Pengaruh Terapi Murottal Surat Ar-Rahman dan Aromaterapi Lavender terhadap Kualitas Tidur pada Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisis di RS Sari Asih Ciputat - Nur Sri Tuti; Hernandia Distinarista; Tutik Rahayu (Journal of Medical Practice and Research, 2026)
Introduction: Hemodialysis is a treatment for chronic kidney failure, one of the side effects of which is sleep disturbance. The purpose of this study was to determine the effect of murottal therapy of Surah Ar-Rahman and lavender aromatherapy on sleep quality in chronic kidney failure patients undergoing hemodialysis. Methods: This type of research is a pre-experimental study with a pretest-posttest design without a control group using a purposive sampling technique with 32 respondents. Data collection used the PSQI questionnaire. Data were collected before and after the intervention was given and then processed statistically using the Wilcoxon test. Results: There is an effect of murottal therapy of the Ar-Rahman letter and lavender aromatherapy on sleep quality in patients with chronic kidney failure undergoing hemodialysis with a p value of 0.000. Conclusions: The application of murottal therapy of the Ar-Rahman letter and lavender aromatherapy can improve the quality of sleep of chronic kidney failure patients undergoing hemodialysis and this intervention can be recommended.